Leontiev e natureza social do psiquismo: das lacunas no texto à totalidade na história - Silva, Rhayane Lourenço da (2013)
Thee present thesis has as its purpose the historical analysis of the works of A.N. Leontiev (1903-1979) to contribute to overcome the superficial readings of his texts, which demote his work to a caricature of Marxism associated to Stalinism. Our hypothesis is that the distorted interpretations of L. S. Vigotski`s works disseminated both in Brazil and around the world try to dissociate him from the Marxism, which also unfolds to a mischaracterization of Leontiev`s works. It is, therefore, justified the realization of an analysis of Leontiev`s works guided by the historical problems placed before him and in the pathways he has chosen to solve them. We want to place the following questioning: How science in Stalinism was done? What is proposed by Leontiev, which is his scientific commitment and how it was executed in a historical context as tortuous as it was? It's our job not connive with mystified visions and seek to realize a more fully analysis of Leontiev's works. Thus, we seek to clarify the main problem that is evident in the work of Leontiev as a whole and understand the vertebral character that the category of activity has in his works in the comprehension of the social nature of the psyque. In our first chapter we achieve a bibliographical revision that allowed us to present the positions defended before the polemic relationship among Vigotski and Leontiev put in by the scholars and disseminated around the world. After that, we stated the existence of interpreters that are positioned clearly in favor of the understanding that there has been a rupture between the works of Vigotski and Leontiev and the authors that are positioned in favor of a complementarity between them. Nevertheless, we observed that as a common ground among the interpreters of both positions is that both corroborate for the dissemination of a vision that encloses a dichotomy between language and labor in the works of Vigotski and Leontiev. We observed gaps left on the historical context of the production of Vigotski and Leontiev by the commenters presented in the first chapter. On the hypothesis that these gaps results of arbitrary interpretation of facts or even by a superficial treatment of the historical context in which they lived, we conducted in the second chapter a study about the history of Soviet Psychology under Stalinism, as primary data of our research about the path taken by Leontiev. With the third and fourth chapters of our work we finish our contributions for the overcoming of the gaps left by fragmented readings of Leontiev's work, placing his works in the entirety of history. In this chapter we have made an exposition of his works demonstrating that the category of activity is a vertebral character to clarify the main problem of his works: the social nature of mind. Thus, we demarcated that the main unity among Leontiev and Vigotski is expressed on the results of these authors facing the dualisms presented in the Psychology and on the centrality of the problem of the social nature of mind.